Oleanane triterpenoids with C-14 carboxyl group from Astilbe grandis inhibited LPS-induced macrophages activation by suppressing the NF-κB signaling pathway - Yue, Lan; Luo, Jinfang; Zhao, Chenliang; Zhao, Jinfeng; Ye, Jianghai; He, Kang; Zou, Juan (Frontiers in Pharmacology, 2024)
Background: Excessive inflammation poses significant risks to human physical and mental health. Astilbe grandis, a traditional Miao medicine, is renowned for its anti-inflammatory properties. However, the specific anti-inflammatory effects and mechanisms of many compounds within this plant remain unclear. This study aims to investigate the anti-inflammatory effects and mechanisms of two characteristic oleanane triterpenoids, 3α-acetoxyolean-12-en-27-oic acid (1) and 3β-acetoxyolean-12-en-27-oic acid (2), isolated from A. grandis, using lipopolysaccharide (LPS)-induced Macrophages.The anti-inflammatory effects and mechanisms of compounds 1 and 2 were investigated by establishing an LPS-induced inflammation model in RAW 264.7 cells and THP-1 cells. Nitric oxide (NO) levels were assessed using the Griess method.The concentrations of tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and interleukin-1beta (IL-1β) were measured via enzyme-linked immunosorbent assay (ELISA). The expression of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) was determined using western blotting and quantitative real-time PCR (qRT-PCR). Additionally, the phosphorylation level of p65 in nuclear factor-kappa B (NF-κB) was assessed through western blotting. The nuclear translocation of NF-κB p65 was assessed through immunofluorescence staining.Finally, the binding affinity of the compounds to NF-κB p65 target was validated through molecular docking.Results: Compounds 1 and 2 significantly inhibited the expression of NO, TNF-α, IL-6, IL-1β, COX-2, and iNOS in LPS-induced Macrophages.Mechanistically, they attenuated the activation of the NF-κB signaling pathway by 2 downregulating the phosphorylation level and nuclear translocation of p65.This study elucidates the anti-inflammatory activities and potential mechanism of the characteristic oleanane triterpenoids with C-14 carboxyl group, compounds 1 and 2, in LPS-induced Macrophages by inhibiting the NF-κB signaling pathway for the first time. These findings suggest that these two compounds hold promise as potential candidates for anti-inflammatory interventions in the future.